Analysis of the problem of low adherence of patients to attendance at outpatient clinics and cardiorehabilitation programs according to the data from published studies - Yu. V. Semenova; N. P. Kutishenko; S. Yu. Martsevich (Столичная издательская компания, 2015)
The aim of this review was to study a problem of outpatient non-attendance by the analysis of relevant literature data. Pubmed and Cyberlenica articles and abstracts, published in 1966-2015, concerning the problem of non-attendance at outpatient clinics and cardiac rehabilitation programs, were used as data sources. The search included articles that reviewed the prevalence of outpatient non-attendance, reasons for it, it's effect on disease outcomes and search for possible ways of its correction. The problem of patients' non-attendance at outpatient clinics and cardiac rehabilitation programs is urgent in many countries and depends on various factors. This problem is best studied from a perspective of its causes. Factors related to the patient himself play the major role, although the influence of factors related to hospital and doctor's characteristics also significantly contribute to the problem. Various methods to improve attendance were suggested. Causes that can be effected by the patient himself or by the doctor at visits: forgetfulness, lack of awareness and motivation. There are few studies that evaluate the effect of non-attendance on medication adherence and outcomes of diseases. Non-attendance at healthcare clinics is a common and urgent issue all over the world. It can affect medication adherence, which is crucial for a long-term regular primary and secondary preventive therapy of cardiovascular diseases. Study of non-attendance at healthcare clinics is an important scientific and clinical problem.